Motivation Profiles, Personal Values, and Personality Traits: The Interplay in Research Management and Administration - José M. R. C. A. Santos; Melinda Fischer; Simon Kerridge (Ital Publication, 2026)
This study addresses a significant gap in the literature by examining the motivation profiles of Research Managers and Administrators (RMAs) and their correlation with personal values and personality traits. Drawing on Self-Determination Theory (SDT), the research sought to propose and validate a conceptual framework specifically for RMAs, introducing the distinct profile of outcome-driven motivation. Empirical data were collected using a quantitative, cross-sectional survey (N=1,095 valid responses) distributed via snowball sampling. The methodological rigor was demonstrated through Exploratory Factor Analysis (EFA), with highly suitable data (KMO=0.915, p<0.001) and high reliability (Cronbach’s alpha ranging from 0.757 to 0.880). The EFA validated the construct of three distinct motivation profiles. RMAs were found to exhibit a predominantly autonomous (intrinsic) drive, confirmed by the highest mean score among the profiles, with statistically significant differences between all three types of motivation. This intrinsic motivation aligns with personal values that emphasize benevolence and universalism while downplaying power and tradition, and personality traits showing high conscientiousness, openness, and agreeableness. This work extends the use of SDT in Science and Technology Studies by validating a specific measurement scale for RMA motivation profiles. The results offer practical guidance, supporting the need for flexible, tailored motivational strategies and policies that enhance intrinsic factors such as autonomy and competency to boost RMA performance.